2016
DOI: 10.1128/jcm.01313-16
|View full text |Cite
|
Sign up to set email alerts
|

Xpert MTB/RIF Assay Shows Faster Clearance of Mycobacterium tuberculosis DNA with Higher Levels of Rifapentine Exposure

Abstract: The Xpert MTB/RIF assay is both sensitive and specific as a diagnostic test. Xpert also reports quantitative output in cycle threshold (CT) values, which may provide a dynamic measure of sputum bacillary burden when used longitudinally. We evaluated the relationship between Xpert CT trajectory and drug exposure during tuberculosis (TB) treatment to assess the potential utility of Xpert CT for treatment monitoring. We obtained serial sputum samples from patients with smear-positive pulmonary TB who were consecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
2
9
0
Order By: Relevance
“…Because the murine studies demonstrated a clear exposure‐response relationship for both rifamycins, another clinical trial (TBTC study 29X) was performed in which rifapentine doses ranged from 10 to 20 mg/kg . As expected, patients with rifapentine plasma exposures in the two higher tertiles had more rapid sputum culture conversion and higher rate of change in Xpert MTB/RIF assays than the lowest tertile . This result corroborated the hypothesis that increasing rifapentine doses would increase efficacy in humans, but again demonstrated that rifapentine doses required to achieve superior efficacy over rifampin were higher than anticipated based on results in mice.…”
supporting
confidence: 61%
“…Because the murine studies demonstrated a clear exposure‐response relationship for both rifamycins, another clinical trial (TBTC study 29X) was performed in which rifapentine doses ranged from 10 to 20 mg/kg . As expected, patients with rifapentine plasma exposures in the two higher tertiles had more rapid sputum culture conversion and higher rate of change in Xpert MTB/RIF assays than the lowest tertile . This result corroborated the hypothesis that increasing rifapentine doses would increase efficacy in humans, but again demonstrated that rifapentine doses required to achieve superior efficacy over rifampin were higher than anticipated based on results in mice.…”
supporting
confidence: 61%
“…Among HIV-negative pulmonary TB patients tested at baseline and at different time points during treatment, the measure of cycle thresholds and relative changes in Ct values (ΔCt) correlated with culture conversion, predicted treatment failure with 75% sensitivity and 89% specificity [55]. In a multicentre trial of rifapentine-based treatment of smear-positive TB, modelling of longitudinal Xpert Ct values (measured at weeks 0, 2, 4, 6, 8 and 12) in relation to drug exposure showed higher ΔCt in subjects receiving rifapentine than in subjects receiving standard-dose rifampin, indicating the potential of Xpert ΔCts as a dynamic measure of response to therapy [56].…”
Section: Molecular Assaysmentioning
confidence: 99%
“…However, this difference may impact the results of molecular identification methods that are used to confirm both the presence of M. tuberculosis complex and genotypic resistance patterns, as these have an operational limit for detection and interpretation. As Xpert MTB/RIF (Cepheid, Sunnyvale, CA, USA) is increasingly being considered as a predictor of treatment outcome, and for diagnostic use in resource-limited settings, this difference may indeed prove important [ 23 , 24 ].…”
Section: Discussionmentioning
confidence: 99%